A detailed description of methyl methacrylate free radical polymerization using different heating policies under isothermal and non-isothermal conditions: a kinetic Monte Carlo simulation. (4th March 2021) - Bairami Habashi, Ramin; Najafi, Mohammad; Mostafaei, Peyman; Shojaei, Behrouz
ABSTRACT: A robust kinetic Monte Carlo (KMC) algorithm was precisely used to investigate and monitor the bulk free radical polymerization of methyl methacrylate (MMA) employing isothermal (ITPs) and non-isothermal (NTPs) heating policies. While temperature was fixed at 50°C (ITP50), 60°C (ITP60), and 70°C (ITP70) in isothermal policies, the non-isothermal policies are based on either a step increase in temperature profile from 50°C to 70°C at 120 or 60 min (NTP1 or NTP2, respectively), or a step decrease from 70°C to 50°C at 20 min (NTP3). The simulation data were in good agreement with the experimental data. It is revealed that the lower the average temperature is, the lower the rate of gel effect becomes. Furthermore, the initial gelation points, maximum gelation points, and glassy region interval are characterized. As a consequence of rising temperature, the initial glassy region shifts to a higher conversion. The maximum polymerization rate was achieved in a conversion range of 55-59%. It was found that temperature reduces average molecular weights and dispersity and narrowed molecular weight distribution (MWD); polymerization time was dropped by 85% too. Finally, NTP1 or NTP2 policies provide a narrower MWD at a higher average molecular weight. Graphical abstract: uf0001